An integrated scenario analysis for future zero‐carbon energy system. (5th March 2015) - Zhang, Qi; Mclellan, Benjamin C.; Li, Hailong
Summary An integrated scenario analysis methodology has been proposed for zero‐carbon energy system in perspectives of social‐economy, environment and technology. By using the methodology, service demands in all sectors were estimated based on social‐economic data, and then the best technology and energy mixes were obtained to meet the service demands. The methodology was applied to Japan toward zero‐carbon energy system out to the year of 2100, and three different scenarios of nuclear power development are considered in light of the Fukushima accident: (i) no further introduction of nuclear, (ii) fixed portion and (iii) no limit of nuclear. The results show that, zero‐carbon energy scenario can be attained in the year 2100 when electricity will supply 75% of total energy consumption, and three power generation scenarios were proposed, 30% renewable and 70% gas‐carbon capture and storage (CCS) in Scenario 1, respective one‐third nuclear, renewable and gas‐CCS in Scenario 2, and 60% nuclear power, 20% renewable and 10% gas‐CCS in Scenario 3. Finally, Scenario 2 is rated as the most balanced scenario by putting emphasis on the availability of diversified power source, considering the inter‐comparison of the three scenarios from the four aspects of cost, CO2 emission, risk and diversity. Copyright © 2015 John Wiley & Sons, Ltd.